Advanced Method for Determining Land Plot’s Physical Surface - Malashevskyi, Mykola; Malashevska, Olena (Geomatics and Environmental Engineering, 2024)
This study examines the issue of the accuracy of physical surface calculations for land plots with complex configurations and reliefs. The goal of the study was to develop a methodology for determining the surface area of land plots with complex configurations and reliefs. The presented model was based on the finite element method. The developed method allows one to evaluate a relief’s complexity by using a dimensionless mean physical surface complexity factor; a Fortran program was developed for the methodology. Experiments that proved the effectiveness of the methodology and a comparative analysis of those areas that were calculated by the presented method and TIN model were carried out. The research findings proved the practicability of the methodology for calculating the physical surfaces of land plots with complex configurations. The presented methodology can be used for flood modeling, landscape and vertical planning, etc.